Women in engineering: stories of attrition and retention - Abri, Janet Huelsen, author; Safarik, Lynn, advisor; Albright, Leonard, committee member; Kreidenweis, Sonia, committee member; Harbour, Clifford P., committee member (Colorado State University. Libraries, 2006)
The number of women choosing to enroll in engineering programs has steadily increased since 1970, but the retention rates for women have drastically decreased despite initiatives to encourage women to enter engineering and graduate. Why do so many women drop out of engineering programs? Why do so few women persist and graduate? What are the experiences that women have that lead them to make their decisions about persisting or attriting from engineering programs? What meaning do they ascribe to their persistence or attrition? Using narrative inquiry and a feminist perspective, this study looked at the stories that women share about their experiences in engineering programs to understand how those experiences impact their decisions to persist or attrit from engineering and to understand how women explain their persistence or attrition to themselves. Although this study focused on engineering majors, the findings may apply to women in mathematics and other science fields as well.
Keywords: higher education; women's studies